INVESTIGATION AND IMPACT MITIGATION OF THE COVID-19 PANDEMIC AT CONTAINER TERMINAL: CASE STUDY OF LAMONG BAY TERMINAL - Suwito M P, Utamining
As part of the global supply chain, hub container ports/terminals play an important role as a link for global trade activities. The disruption of the COVID-19 pandemic to several social and economic activities in the hinterland and foreland has indirectly impact on port activities. Based on some research, during the COVID-19 pandemic, several productivity declines were found in several international ports in the world, especially in Asia, The United States and Europe. To reveal the magnitude of the impact from the other side of the region, specifically in Indonesia, a study was conducted to investigate the impact focus related to the productivity and operational performance of port/container terminals in this country, through the Lamong Bay Terminal as case study. The research was conducted by examining several variables including the variable number of cases and deaths of COVID-19, the variable number ship calls, the variable flow of containers, and port operational performance. In addition, a review was also conducted on the relationship between the variables number of cases and deaths of COVID-19 to the change of ship calls variable and container flow variable. The result of the study show that a significant impact is only found or can be explained through the relationship between certain variables and for a certain period of time, namely the number of COVID-19 deaths in Asia and Australia on the difference (?) flow of international container exports at time gap 11; the number of COVID-19 cases in Asia and Australia to the difference (?) flow of domestic containers in the second half of 2020; as well as the number of cases and deaths of COVID-19 in Indonesia against difference (?) international ship call in the second half of 2021. Likewise, the result of operational performance assessments during the COVID-19 pandemic occurred, where the majority were in good and quite good scores, except for B/S/H domestic. So that the mitigation of the COVID-19 pandemic that is considered appropriate is increasing connectivity; rationalization of cost, tariff, and revenues; as well as consistency in the development of automation and digitization.